Stressor-Induced “Inflammaging” of Vascular Smooth Muscle Cells via Nlrp3-Mediated Pro-inflammatory Auto-Loop - Herrmann, Jaqueline; Xia, Mengdi; Gummi, Manasa Reddy; Greco, Anna; Schacke, Annika; van der Giet, Markus; Tölle, Markus; Schuchardt, Mirjam (Frontiers in Cardiovascular Medicine, 2021)
Calcification of the vessel wall as one structural pathology of aged vessels is associated with high cardiovascular mortality of elderly patients. Aging is linked to chronic sterile inflammation and high burden of reactive oxygen species (ROS), leading to activation of pattern recognition receptors (PRR) such as Nlrp3 in vascular cells. The current study investigates the role of PRR activation on the calcification of vascular smooth muscle cells (VSMC). Therefore, in vitro cell culture of primary rat VSMC and ex vivo aortic stimulation were used and osteogenic, senescence and inflammatory markers were analyzed via real-time PCR, in situ RNA hybridization, Western Blot, photometric assays and histological staining. Induction of ROS and DNA-damage by doxorubicin induces a VSMC phenotype shift towards the expression of osteogenic, senescence and inflammatory proteins. Induction of calcification is dependent on Nlrp3 activity. Il-1β as a downstream target of Nlrp3 induces the synthetic pro-calcifying VSMC phenotype. Inhibition of PRR with subsequent reduction of chronic inflammation might be an interesting target to reduce calcification of VSMC and subsequently the cardiovascular mortality of patients suffering from vessel stiffness.